Perancangan Interior Pusat Pendidikan Fashion di Kota Samarinda - Livia Gabrielle William (Intra, 2016)
Interior Education Center Fashion in Samarinda City aims to find education center of fashion that can complete student’s facilities, finding educational center of fashion that produces interior design educational, informative, and presentative, find educational center of fashion which can show elements of Indonesian culture, discover fashion education center that can attract people in Samarinda. The expected benefits of this research is for the public forum for people who have become fashion designers, facilities can increase insight into fashion both for students and the community in the form of libraries, information centers, galleries clothing, fashion show.The a dvantages for the author of this research is to increase the knowledge and experience of how to study fashion education center and is able to improve the capability and mindset of a interior. The methods used are design thinking method of Bryan Lawson his book entitled How Designer Think Fourth passing through three phases: intention, aspiration phase, and stage practices. There are three stages of data collection in design thinking method as to perform data collection, analysis design, programming, concept design, schematic design, to the final product of the design.